Differentiation of extracted gelatins from porcine, bovine and chicken origins based on their physical, chemical and structural properties using analytical techniques - Jamaluddin, Juhazliana; Abbasiliasi, Sahar; Sazili, Awis Qurni; Mustafa, Shuhaimi (Hibiscus Publisher Enterprise, 2024)
Physicochemical properties of extracted gelatins from porcine, bovine and chicken sources compared to that of commercial bovine and porcine gelatins have been determined. Gelatin samples were assessed for their pH, water holding capacity, fat binding capacity, foaming capacity and stability, structural properties, thermal and amino acid profiles and molecular weight distribution. There were significant differences (P<0.05) in pH, water holding capacity, fat binding capacity, foaming stability and foaming capacity between gelatins. Porcine, bovine and chicken gelatins had two prominent bands which were visible in the α-chain region in the range of ~135 to ~100 kDa. Highest gelling point value was observed in extracted chicken gelatin while the highest value of melting point, were in commercial porcine and extracted chicken gelatins. Glycine, hydroxyproline, proline, alanine, arginine and glutamic acid were found to be the major amino acids. Physicochemical properties of gelatins could be characterized using analytical techniques.